INFORMATION COMPETENCY AS A BASIS OF PROFESSIONAL ACTIVITY OF THE TEACHER OF THE FUTURE - Kazachek, Natalia; Starostina, Svetlana; Tokareva, Julia; Fedotova, Alena (Revista Inclusiones, 2020)
The problem of professional formation and development of the teacher of the future in the context of digitalization of education and knowledge economy requires more in-depth and targeted research. This work deals with theoretical substantiation, development and technologies of forming information competencys on the basis of the life cycle of teachers of the future knowledge against the background of global digitalization. The main research methods of research are comparative analysis of research in knowledge management and ICT competency development, expert assessments and statistical methods of data processing. The study concludes that knowledge management should serve as the theoretical basis for the organization of the educational process. The condition for the implementation of knowledge management theory in the educational process are information and personalised approaches.